Koncepcja migracji E. S. Lee, jej weryfikacja i ocena - Skrobiszowa, Barbara (Wydział Prawa i Administracji UAM, 1981)
Confirmation of concordance of hypotheses contents with facts, generally observed, allows to modify them into statements. Hypotheses of E. S. Lee's migration concept were derived and tested by the author on the ground of data from capitalist economy (mainly the U.S.). They call for verification for various areas and in various time periods. Such verification is enabled by the material collected in Poland on internal persistent migrations in the years 1950 - 1978, i.e. under conditions determined by socialist socio-economic system. Hypotheses verification is the purpose of the article and it is its basic content. No comprehensive research is assumed. The results of the verification, by which the theory is consolidated, as well as its presentation with contemporary and posterior research on migration, allow to evaluate the work positively.
E. S. Lee's Concept of Migration. Its Verification and Evaluation